METODE DRILL DALAM PENINGKATAN KETERAMPILAN DASAR ROLLING SENAM LANTAI: Indonesia - Fajri, Ahmad (INSPIREE: Indonesian Sport Innovation Review, 2020)
The study purpose: Efforts to improve basic skills in gymnastics forward rolling perfectly, there must be anappropriate teaching method for this material. One of the teaching methods that the writer considers appropriateis the drill method.Materials and methods: In this study using a classroom action research technique that has 2 tests (cycle 1 andcycle 2). The test taken from the sample used the rolling test skills test in gymnastics.Results. 32 samples were tested, in cycle 2 there were 27 students categorized as 'successful or complete' and 5students 'incomplete' in carrying out the basic skills of rolling floor gymnastics ahead.Conclusions: The advanced rolling gymnastics skills carried out by students are increasingly improving andperfect, this shows satisfactory results and there is a significant increase in elementary school students.